Analysis and experimental investigation of a current controller for a full-bridge boost rectifier - Chan, Chok You (2013)
The development of a current controller with inherent integral action for a full-bridge boost rectifier is presented. The main control objectives are to achieve dc output voltage regulation and near-unity power factor in the presence of unknown load. The stability analysis of the current-controlled rectifier system is carried out using Floquet theory. Some experimental results are also presented to verify the effectiveness of the control method.